Immunity and infection : emerging and developed market sovereign spreads over the global financial crisis (2018)
We compare sovereign bond spreads during the international financial crisis across groups drawn from 43 countries, including 20 emerging economies. We extend traditional factor analyses and utilize propensity score matching to select a non-crisis sample for comparison with the crisis sample that is more robust to exogenous crisis dating. We find minimal changes over the crisis period in the average spreads of local-currency-denominated emerging market bonds. In contrast, the spreads of peripheral Eurozone sovereign bonds increased by large amounts and were subject to sovereign risk contagion.